p53 regulates epithelial–mesenchymal transition and stem cell properties through modulating miRNAs - Chang, Chun-Ju; Chao, Chi-Hong; Xia, Weiya; Yang, Jer-Yen; Xiong, Yan; Li, Chia-Wei; Yu, Wen-Hsuan; Rehman, Sumaiyah K.; Hsu, Jennifer L.; Lee, Heng-Huan; Liu, Mo; Chen, Chun-Te; et al. (Nature cell biology, 2011)
The epithelial to mesenchymal transition (EMT) has been recently associated with a stem cell phenotype. In breast cancer cell lines and tumours, p53 directly targets the expression of microRNAs that have been shown to inhibit EMT and stem cells regulators. The epithelial–mesenchymal transition (EMT) has recently been linked to stem cell phenotype 1 , 2 . However, the molecular mechanism underlying EMT and regulation of stemness remains elusive. Here, using genomic approaches, we show that tumour suppressor p53 has a role in regulating both EMT and EMT-associated stem cell properties through transcriptional activation of the microRNA miR-200c. p53 transactivates miR-200c through direct binding to the miR-200c promoter. Loss of p53 in mammary epithelial cells leads to decreased expression of miR-200c and activates the EMT programme, accompanied by an increased mammary stem cell population. Re-expressing miR-200c suppresses genes that mediate EMT and stemness properties 3 , 4 and thereby reverts the mesenchymal and stem-cell-like phenotype caused by loss of p53 to a differentiated epithelial cell phenotype. Furthermore, loss of p53 correlates with a decrease in the level of miR-200c, but an increase in the expression of EMT and stemness markers, and development of a high tumour grade in a cohort of breast tumours. This study elucidates a role for p53 in regulating EMT–MET (mesenchymal–epithelial transition) and stemness or differentiation plasticity, and reveals a potential therapeutic implication to suppress EMT-associated cancer stem cells through activation of the p53–miR-200c pathway.